2011
DOI: 10.1253/circj.cj-11-0135
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Westernization of Etiology and Clinical Characteristics of Heart Failure Patients in Japan

Abstract: on behalf of the CHART-2 Investigators Background: Hospitalization due to acute heart failure syndrome (AHFS) is an indicator of worsened prognosis for patients with cardiovascular disease (CVD). The Chronic Heart Failure Analysis and Registry in the Tohoku District 2 (CHART-2) Study was designed to elucidate characteristics and prognosis of patients at high risk for CVD progression due to AHFS. Methods and Results:The CHART-2 Study is a prospective observational multicenter cohort study. Patients with overt H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 224 publications
(231 citation statements)
references
References 36 publications
9
216
5
1
Order By: Relevance
“…The external validation of our score must be evaluated in other cohort studies, although a lack of external validation is a common problem with the existing Japanese risk prediction tools, including the NIPPON DATA 80, JALS, JMS cohort and Hisayama study. Considering the increasingly Westernized lifestyle in urban areas 52) , these tools should be re-evaluated using a consortium of cohort studies, which include both urban and rural areas, such as the Epoch-Japan study group 53) . Very recently, the new AHA/ACC Guideline on the Treatment of Blood Cholesterol recommended the use of the new Pooled Cohort Equations to estimate the 10-year CHD risk in both white and black males and females, aged 40-75 years, and the FRS is no longer used for risk assessment 54) .…”
Section: Discussionmentioning
confidence: 99%
“…The external validation of our score must be evaluated in other cohort studies, although a lack of external validation is a common problem with the existing Japanese risk prediction tools, including the NIPPON DATA 80, JALS, JMS cohort and Hisayama study. Considering the increasingly Westernized lifestyle in urban areas 52) , these tools should be re-evaluated using a consortium of cohort studies, which include both urban and rural areas, such as the Epoch-Japan study group 53) . Very recently, the new AHA/ACC Guideline on the Treatment of Blood Cholesterol recommended the use of the new Pooled Cohort Equations to estimate the 10-year CHD risk in both white and black males and females, aged 40-75 years, and the FRS is no longer used for risk assessment 54) .…”
Section: Discussionmentioning
confidence: 99%
“…For calculation of PS, we used a logistic regression model in which the treatment status of loop diuretics was regressed for the following 31 baseline characteristics: age, male sex, systolic and diastolic blood pressure (SBP and DBP), heart rate, BMI, New York Heart Association (NYHA) class, history of hospitalization for HF, hypertension, attending physician(s) at each hospital and was confirmed by one independent physician who was a member of the Tohoku Heart Failure Association. 15 …”
Section: Subjects and Inclusion Criteriamentioning
confidence: 99%
“…54, 55 Our recent studies have also revealed an increasing trend towards ischemic etiology and comorbidities with DM and HT in Japanese HF patients. 10 The CHART-1 study, which enrolled . Recent trend towards ischemic etiology for heart failure in Asia.…”
Section: Burden Of Ischemic Etiology Of Hf In Asiamentioning
confidence: 99%
“…Recent trend towards ischemic etiology for heart failure in Asia. In both Japan (CHART studies) 10 and China, 18 the prevalence of coronary artery disease (CAD), hypertension (HT) and diabetes (DM) increased as a cause or comorbidity of heart failure. HF Epidemiology in Asia β-blockers, ACEI/ARB, diuretics and aldosterone antagonists, 16 although there are few reliable data.…”
Section: Burden Of Ischemic Etiology Of Hf In Asiamentioning
confidence: 99%